2015
DOI: 10.1007/s10336-015-1304-4
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal studies confirm faster telomere erosion in short-lived bird species

Abstract: Evidence is accumulating that telomeres become shorter with advancing age and possibly explain some of the observed variation in longevity. Cross-sectional analyses have shown that species with shorter lifespans lose more telomeric repeats with age than species with longer lifespans. Using existing data from longitudinal studies performed on several bird species, we confirmed a negative relationship between the rate of telomere shortening and maximum longevity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 19 publications
(28 reference statements)
3
31
0
Order By: Relevance
“…The number of longitudinal studies in natural populations indicating telomere erosion with age slowly, but persistently increases (Dantzer and Fletcher 2015; Sudyka et al 2016). However, the causal involvement of telomeres in ageing process still remains an open question (Simons 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of longitudinal studies in natural populations indicating telomere erosion with age slowly, but persistently increases (Dantzer and Fletcher 2015; Sudyka et al 2016). However, the causal involvement of telomeres in ageing process still remains an open question (Simons 2015).…”
Section: Discussionmentioning
confidence: 99%
“…We used relative TL, expressed as the ratio ( T / S ) of a telomere copy number ( T ) and a single control gene copy number ( S , which was GAPDH, (Cawthon 2002)). We used the primers designed for zebra finch but these have been previously validated for the blue tit by us (see Sudyka et al 2014, 2016). To generate a standard curve for amplification efficiency, each plate included serial twofold dilutions of a reference DNA (mixed DNA of five birds not included in the study) run in duplicate from 10 to 0.31 ng for telomere and from 10 to 0.62 ng for GAPDH.…”
Section: Methodsmentioning
confidence: 99%
“…Without this, it is difficult to argue that telomere shortening is a relevant cost or a biomarker related to reproductive activity. Regardless of the fact that telomeres shorten more slowly in long‐lived animals, in short‐lived species (or, as mentioned earlier—in ectotherms) telomere erosion may not be a sufficient condition to trigger senescence (ultimately leading to death). Even though (reproductive) senescence is widely observed in the wild, animals often die before getting old due to extrinsic mortality (predation, disease, resource depletion, etc.…”
Section: Studies Published To Date Have Many Limitationsmentioning
confidence: 96%
“…In a study on rodents, no relationship between maximum lifespan and telomere length was detected (Seluanov et al, 2007). In birds, absolute telomere length does not seem to relate to variation in lifespan between species; however, longer-lived avian species seem to have lower rates of telomere shortening than shorter-lived species (Dantzer & Fletcher, 2015;Haussmann et al, 2003;Sudyka, Arct, Drobniak, Gustafsson, & Cichoan, 2016;Tricola et al, 2018). This relationship between rate of telomere loss and maximum lifespan in birds may be caused by variation between species in how well telomeres are maintained throughout their lifespan.…”
Section: Both Longitudinal and Cross-sectional Studies In Birds Showmentioning
confidence: 98%
“…In mammals, a comparative study found that short-lived, small species have longer telomeres and higher telomerase expression than long-lived, large species (Gomes et al, 2011). In birds, absolute telomere length does not seem to relate to variation in lifespan between species; however, longer-lived avian species seem to have lower rates of telomere shortening than shorter-lived species (Dantzer & Fletcher, 2015;Haussmann et al, 2003;Sudyka, Arct, Drobniak, Gustafsson, & Cichoan, 2016;Tricola et al, 2018). In birds, absolute telomere length does not seem to relate to variation in lifespan between species; however, longer-lived avian species seem to have lower rates of telomere shortening than shorter-lived species (Dantzer & Fletcher, 2015;Haussmann et al, 2003;Sudyka, Arct, Drobniak, Gustafsson, & Cichoan, 2016;Tricola et al, 2018).…”
Section: Both Longitudinal and Cross-sectional Studies In Birds Showmentioning
confidence: 99%